2019
DOI: 10.1186/s12955-019-1230-x
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D-5L utilities per health states in Spanish population with knee or hip osteoarthritis

Abstract: BackgroundThe objective of this study was to obtain utilities by means of EQ-5D-5L for different health states in patients with knee osteoarthritis (KOA) or hip osteoarthritis (HOA) in Spain, and to compare these values with those used in foreign studies with the aim of discussing their transferability for their use in economic evaluations conducted in Spain.MethodsPrimary study: Observational prospective study of KOA or HOA patients in Spain. Sociodemographic and clinical characteristics were collected to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
0
11
2
Order By: Relevance
“…No disutility due to AEs was applied in the model as this is already accounted for by the utility value of the health state [ 33 ]. Furthermore, discontinuation due to AEs was not considered in the model.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…No disutility due to AEs was applied in the model as this is already accounted for by the utility value of the health state [ 33 ]. Furthermore, discontinuation due to AEs was not considered in the model.…”
Section: Methodsmentioning
confidence: 99%
“…No relevant utility data was identified in the targeted literature review for a Japanese population with OA, although a patient-reported outcome study using the EQ-5D-5L questionnaire was identified that reported the utility values of the included health states for a Spanish population [ 33 ]. These values accounted for the baseline utility of the disease (OA of the knee or hip), the treatment (non-opioid, opioid, surgery and post-surgery), and the disutility due to the treatment (AEs) (Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EQ-5D-5L is a generic instrument designed to measure dimensions of health relevant to all health states, including healthy individuals, and not patients' perception of aspects of health specifically affected by OALL. However, it has the advantage of allowing us to attribute patients' preferences to the described health status in patients with OALL and to compare them between different populations [48].…”
Section: Limitationsmentioning
confidence: 99%